The Effect of Task-Based Collaborative Learning on Students’ Mathematical Physics Learning Outcomes at Universitas Muhammadiyah Makassar - Dewi Hikmah Marisda (Jurnal Pendidikan Fisika, 2019)
The unevenness of the basicmathematicalabilities possessed by physics students causes the mastery of Mathematical Physics (FISMAT) material to be uneven and the learning outcomes of some students are low. In addition, students self-confidence in asking lectures is also a serious problem. Likewise the development of the present time causes the character of students to be more individual and tend to not want to help their friends in mastering lecture material. Based on the foregoing, the purpose of this study is to find a learning model scenario that is in accordance with the character and content of the FISMAT course material which also minimizes the individual attitudes of students who can certainly support the improvement of the quality of lectures. To achieve this goal, a task-based collaborative learning model is offered in the Mathematics Physics lecture FISMAT. The stages in this esearch that will be carried out to achieve these objectives include : first, the stage of identification, analysis, design, trial and revision; second, designing research instruments and implementing the expected results, namely obtaining a task-based collaborative learning model inMathematics Physics learning (FISMAT). The data obtained will be analyzed qualitatively and quantitatively. The output of this study is a nationally accredited scientific publication, namely the Journal Of Physics Education (JPF) of the   University of Muhammadiyah Makassar. While the additional output produced is a Mathematical Physics (FISMAT) questions module with different levels of difficulty.Key words: Mathematical Physics (FISMAT), Learning Outcomes, Assignments, Collaborative Learning.Ketidakseragaman kemampuan matematika dasar yang dimiliki oleh mahasiswa fisika menyebabkan penguasaan materi Fisika Matematika (FISMAT) menjadi tidak merata dan hasil belajar sebagian mahasiswa rendah. Selain itu, ketidakpercayaan diri mahasiswa untuk bertanya kepada dosen juga menjadi masalah serius. Begitupun perkembangan zaman saat ini menyebabkan karakter mahasiswa menjadi lebih individual dan cenderung tidak mau membantu temannya dalam penguasaan materi kuliah. Berdasarkan hal tersebut di atas, maka tujuan penelitian ini adalah menemukan suatu skenario model pembelajaran yang sesuai dengan karakter dan muatan materi mata kuliah FISMAT yang juga meminimalisir sikap individual mahasiswa yang tentunya dapat menunjang peningkatan kualitas perkuliahan. Untuk mencapai tujuan tersebut, ditawarkan model pembelajaran kolaboratif (Collaborative Learning) berbasis tugas pada perkuliahan Fisika Matematika (FISMAT). Tahapan-tahapan pada penelitian ini yang akan dilakukan untuk mencapai tujuan tersebut meliputi: pertama, tahap identifikasi, analisis, merancang, uji coba dan revisi; kedua, merancang instrument penelitian dan mengimplementasi hasil yang diharapkan yaitu diperolehnya suatu model pembelajaran kolaboratif (Collaborative Learning) berbasis tugas pada pembelajaran Fisika Matematika (FISMAT). Data yang diperoleh akan dianalisis secara kualitatif dan kuantitatif. Luaran dari penelitian ini adalah publikasi ilmiah berupa jurnal nasional terakreditasi yaitu pada Jurnal Pendidikan Fisika (JPF) Universitas Muhammadiyah Makassar. Sedangkan luaran tambahan yang dihasilkan berupa modul soal-soal Fisika Matematika (FISMAT) dengan tingkat kesukaran yang berbeda.Kata kunci: Fisika Matematika (FISMAT), Hasil Belajar, Pemberian Tugas, Pembelajaran Kolaboratif